EP-681 Adherence to VTE prophylaxis guidelines in general surgical patients: a single-centre study. (9th August 2022) - Songra, Lalana; Hussein, Aliyah; Baker, D
Abstract: Introduction: Hospital acquired venous thromboembolism (VTE) is potentially preventable yet still accounts for 60% of all VTE seen. This study aimed to establish adherence to guidelines on VTE prevention including completion of VTE risk assessment within 24 hours of admission and appropriate prescription of mechanical and pharmacological VTE prophylaxis. Methods: A database of all general surgical inpatients in our hospital at any point during the 48-hour period from 21/12/2021 to 22/12/2021 was obtained. Electronic records were examined to check for the presence of 11 established risk factors for VTE and to check for adherence to VTE guidelines. Every surgical patient was reviewed to check whether they were wearing anti-embolic stockings. Standard statistical analyses were undertaken. Results: There were 107 general surgical patients in hospital during the study period. Of these, 33 (31%) had 3 or more risk factors on admission for VTE. 106 (99%) patients had VTE assessments completed within 24 hours of admission. Of these 107 patients, 93 (87%) had appropriate pharmacological VTE prophylaxis or had a documented reason why this was not prescribed. 14 (13%) patients had no pharmacological VTE prophylaxis prescribed. 84 patients were assessed as requiring anti-embolic stockings. Of these, 57 (68%) of patients were prescribed stockings, and 30 (36%) were physically wearing stockings. Conclusions: This study has shown that adherence to VTE guidelines among surgical patients in our hospital is substandard. We suggest having a VTE safeguard during the ward round responsible for identifying any deficits in VTE prophylaxis and ensuring recommendations are acted upon.